2012
DOI: 10.1108/17505931211241341
|View full text |Cite
|
Sign up to set email alerts
|

The effects of visual information in eWOM communication

Abstract: PurposeElectronic word of mouth (eWOM) is a considerably influential factor for consumers to search for product information. Nowadays, consumers can easily post visual information (e.g. pictures or videos) to convey product information and consumption‐related experiences. Yet, prior eWOM studies focused primarily on the verbal information of eWOM. Few studies have paid sufficient attention to the effects of visual information in eWOM communication. The purpose of this paper, therefore, is to employ blogs to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
2
19

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(144 citation statements)
references
References 44 publications
(61 reference statements)
6
109
2
19
Order By: Relevance
“…In a similar vein, since 'most' consumers might not trust some of the online vendors; they are highly likely to rely on other consumers when making purchasing decisions. Consistent with Lin et al (2012), this study found that (e)WoM affects repurchase intentions. This is probably because third party information source is seen to be more credible than information coming from an online retail vendor.…”
Section: Discussion Of Findingssupporting
confidence: 82%
See 1 more Smart Citation
“…In a similar vein, since 'most' consumers might not trust some of the online vendors; they are highly likely to rely on other consumers when making purchasing decisions. Consistent with Lin et al (2012), this study found that (e)WoM affects repurchase intentions. This is probably because third party information source is seen to be more credible than information coming from an online retail vendor.…”
Section: Discussion Of Findingssupporting
confidence: 82%
“…This is an indication that customers of reputable vendors will engage in (e)WoM for the vendors and patronise their brands. Lin, Lu and Wu (2012) examined the effect of corporate image and relationship marketing on trust and consumer purchase intention and found that corporate image signifi cantly and positively impacts on consumers' purchase intentions; and word-of-mouth enhances this effect. From these fi ndings, it is safe to conclude that vendors' reputation and (e)WoM infl uence shoppers' repurchase intentions online.…”
Section: Vendor Reputation (Vrp) (E)wom Effect and Repurchase Intentmentioning
confidence: 99%
“…Harris and Dennis (2011) further argued that young adults particularly welcome the idea of combining their shopping experience with Facebook. Social media users often share style or fashion-related information with their peers in order to receive some kind of feedback from them (Lin, Lu, & Wu, 2012;Wolny & Mueller, 2013). Most consumers rely on social networking platforms for search purposes, brand inspections, and shopping (Bilgihan, Peng, & Kandampully, 2014).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Although there are numerous articles on social media in the form of whitepapers and blogs, literature in the form of academic research is still in its infancy. Practitioners and marketers seek to benefit from the understanding of how customers manage, create and share user-generated information along with a broader knowledge of WOM's overall role in the decision making process [39,40].…”
Section: Resultsmentioning
confidence: 99%